2006
DOI: 10.1002/chin.200701240
|View full text |Cite
|
Sign up to set email alerts
|

The Unpredictability of Odor

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…First, that molecular shape is an adequate predictor of smell (2,30,32), which currently seems unlikely (33,34). In fact, Drosophila has only 62 olfactory receptors (35), suggesting that a single receptor must generally respond to multiple odorants, but in addition that a single odorant can activate multiple receptors (10,15).…”
Section: Discussionmentioning
confidence: 99%
“…First, that molecular shape is an adequate predictor of smell (2,30,32), which currently seems unlikely (33,34). In fact, Drosophila has only 62 olfactory receptors (35), suggesting that a single receptor must generally respond to multiple odorants, but in addition that a single odorant can activate multiple receptors (10,15).…”
Section: Discussionmentioning
confidence: 99%
“…One theory is that the odorant fits the receptor like a 'lock and key', similarly to the previous §2. However, designing odorants based on such shape complementarity between receptor and odorant (analgous to the substrate and enzyme) proves that this theory alone is not sufficient to explain olfactory response [25]. For one thing, very diversely shaped molecules can initiate the same receptor and conversely some sameshaped molecules initiate non-mutual receptors, such that the receptors are often referred to as simultaneously 'discriminatory' and 'promiscuous'.…”
Section: Olfactionmentioning
confidence: 99%
“…Ninety years later, in his review "On the Unpredictability of Odor," Charles Sell concluded that there are no molecular features of the odorant that directly determine perceptive quality and that it "would seem that consistently accurate prediction of odors are not possible for a very considerable time" (Sell, 2006). Further complicating this situation, interactions between physical properties (e.g.…”
Section: The Stimulusmentioning
confidence: 99%